2019
DOI: 10.1007/978-3-030-17953-3_26
|View full text |Cite
|
Sign up to set email alerts
|

Sparsity of Integer Solutions in the Average Case

Abstract: We examine how sparse feasible solutions of integer programs are, on average. Average case here means that we fix the constraint matrix and vary the right-hand side vectors. For a problem in standard form with m equations, there exist LP feasible solutions with at most m many nonzero entries. We show that under relatively mild assumptions, integer programs in standard form have feasible solutions with O(m) many nonzero entries, on average. Our proof uses ideas from the theory of groups, lattices, and Ehrhart p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

6
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…For other results regarding sparsity, see [3,10,19] for general A and [5,6,7,22] for matrices that form a Hilbert basis. See also the manuscript of Aliev et al [1], who give improved sparsity bounds for feasible solutions to special classes of integer programs and provide efficient algorithms for finding such solutions.…”
Section: Aliev Et Al [2] Established Thatmentioning
confidence: 99%
“…For other results regarding sparsity, see [3,10,19] for general A and [5,6,7,22] for matrices that form a Hilbert basis. See also the manuscript of Aliev et al [1], who give improved sparsity bounds for feasible solutions to special classes of integer programs and provide efficient algorithms for finding such solutions.…”
Section: Aliev Et Al [2] Established Thatmentioning
confidence: 99%
“…Sparsity of solutions to linear Diophantine equations is relevant for the theory of compressed sensing for integer-valued signals [17,18,24], motivated by many applications in which the signal is known to have integer entries, for instance, in wireless communication [31] and in the theory of error-correcting codes [10]. Support minimization was also investigated in connection to integer optimization [2,16,29,30]. Also, numerous applications to combinatorial optimization problems have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Upper bounds on σ(b) under this assumption were studied in [2,6]. Furthermore, Oertel et al [31] showed that asymptotic densities of σ can be bounded using the minimum absolute determinant of A or the 'number of prime factors' of the determinants. If, in addition, A has the Hilbert basis property (i.e., if the columns of A correspond to a Hilbert basis of the cone generated by A), then bounds on σ(b) can be given solely in terms of m. Cook et al [15] showed that if σ(b) < ∞, then σ(b) ≤ 2m − 1; this was improved to σ(b) ≤ 2m − 2 by Sebő [36].…”
mentioning
confidence: 99%